The Relationship Between Gratitude And Meaning Of Life With Post-Traumatic Growth In Teenagers From Broken Homes - Yunis Futihat Rohmawati; IGGA Noviekayati; Anrilia E.M Ningdyah (CV. ITTC INDONESIA, 2026)
This research aims to examine the relationship between gratitude and meaning in life with post-traumatic growth (PTG) in adolescents from broken homes. Broken home is a family condition that has the potential to cause traumatic experiences for teenagers, but it does not always result in negative psychological impacts. This study uses a quantitative approach with a correlational design. The research subjects consisted of 302 teenagers from broken homes who were selected using purposive sampling technique. Data were collected using the Post Traumatic Growth Inventory Scale, Gratitude Questionnaire (GQ-6), and Meaning in Life. They were then analyzed using multiple linear regression. The analysis results show that gratitude and meaning in life simultaneously contribute significantly to predicting PTG. Partially, gratitude and meaning in life also have a positive and significant relationship with PTG. This study concludes that PTG in adolescents from broken homes is influenced by positive psychological resources, particularly gratitude and the ability to find meaning in life, which help adolescents interpret traumatic experiences adaptively and encourage post-traumatic growth.